KEBIJAKAN PEMBINAAN ANAK DIDIK PEMASYARAKATAN DI LEMBAGA PEMBINAAN KHUSUS ANAK BANDUNG BERDASARKAN SISTEM PERADILAN PIDANA ANAK - Oci Senjaya (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2018)
Children are social beings who have equal rights with other creatures, therefore there is not every human or other party who may usurp the right to life and independence. The research method used is qualitative, with a juridical-normative approach. The type of research is descriptive because it is intended to describe the conditions in the Child Development Institution, and how to guide it. This study uses qualitative methods. The focus of the research is fostering Correctional Students in Child Correctional Institutions (LPKA). Tools and data collection used in this study are secondary data. The data is then analyzed using qualitative analysis techniques with interactive analysis models. Based on the results of the research The implementation of Guidance for Children in Correctional Institutions for special children (LPKA) in general has been in accordance with the laws and regulations, facilities and infrastructure for child correctional institutions (LPKA) must be optimized, and constraints remain, efforts made to overcome obstacles in the process of fostering correctional students in accordance with the mandate of Law Number 11 of 2012 concerning Children Criminal Justice System.